2017
DOI: 10.20961/jkpk.v2i1.8530
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Natural Ni/Zeolite Activated by Acid as Catalyst for Synthesis Biodiesel from Ketapang Seeds Oil

Abstract: ABSTRAKTujuan penelitian ini untuk Mengetahui pengaruh penambahan Ni terhadap nilai keasaman, dan Mengetahui kombinasi terbaik katalis dari nikel dan zeolit yang teraktivasi asam sebagai catalitic cracking pada proses pembuatan biodiesel dari minyak biji ketapang. Zeolit diaktivasi dengan menggunakan HCl 4 M. Pembuatan katalis Ni/Zeolit dengan merendam katalis zeolit ke dalam larutan Ni(NO3)2.6H2O dengan variasi konsentrasi 0 %, 5%, dan 10%.Karakterisasi ter-hadap katalis meliputi : XRD,SEM dan FTIR.Hasil Pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Meanwhile the conversion reached 95.54% at 800°C using 0.30 mol/L Ni metal concentration and 94.78% at 700°C using the same Ni metal concentration. This showed that there is an effect of the concentration of metallic Ni which is deposited to open the pores on the catalyst and increase the cracking efficiency (Zhang et al, 2021;Mahmudah & Hari Kusumawati, 2020;Ramadhani et al, 2017). (Endarko & Adawiyah, 2019).…”
Section: Effect Of Cracking Process Temperature and Ni Concentrationmentioning
confidence: 98%
“…Meanwhile the conversion reached 95.54% at 800°C using 0.30 mol/L Ni metal concentration and 94.78% at 700°C using the same Ni metal concentration. This showed that there is an effect of the concentration of metallic Ni which is deposited to open the pores on the catalyst and increase the cracking efficiency (Zhang et al, 2021;Mahmudah & Hari Kusumawati, 2020;Ramadhani et al, 2017). (Endarko & Adawiyah, 2019).…”
Section: Effect Of Cracking Process Temperature and Ni Concentrationmentioning
confidence: 98%
“…Nilai keasaman pada suatu katalis sangat mempengaruhi aktifitas katalis dalam perengkahan [9], dikarenakan dalam reaksi perengkahan diperlukan katalis yang memiliki situs asam aktif yang banyak agar produk dapat terbentuk dengan optimal [10].…”
Section: Pendahuluanunclassified
“…Optimizing the hydrocracking process necessitates the use of catalysts. Research indicates that catalysts for biofuel hydrocracking vary based on the feedstock type, with key characteristics like porosity, surface area, and crystal size significantly impacting their effectiveness [3,4]. Mesoporous silica, with its orderly, interconnected pore network ranging from 2 to 50 nanometers, is vital in hydrocracking [5].…”
Section: Introductionmentioning
confidence: 99%